COMPARISON OF TENSILE STRENGTH OF L-PRF AND A-PRF USING LSCC TECHNIQUE WITH COMMERCIALLY AVAILABLE GTR MEMBRANE - Nadeem Hafeez Khokhar; Abdul Samad Khan; Abdur Rehman; Wasif Iqbal; Hina Imran; Syed Junaid Mehmood (Pakistan Oral & Dental Journal, 2023)
Platelet Rich Fibrin (PRF) has gained tremendous awareness in recent years to be used in wide variety of medical field for soft tissue regeneration including regenerative periodontal therapy. PRF also termed as L-PRF is an autologous autogenous biomaterial consisting of growth factors and cytokines which provide the optimal environment for tissue regeneration and wound healing. A fairly new concept to dentistry is the lowâ€speed centrifugation concept (LSCC). According to this theory, leukocyte infiltration into the red blood cell fraction can be reduced by lowering the relevant centrifugation force (RCF) or g force and increasing spin time. Hence the PRF clot produced will have a looser fibrin structure gradually enhancing the release of leukocytes and growth factors. This PRF type is termed as advanced PRF (A-PRF). The impact of tensile strength of A-PRF in comparison with L-PRF and commercially available GTR membrane is evaluated in this study. Blood samples were collected from a total of 40 volunteers in 10 cc plain vacuum glass tubes without anticoagulant. Blood samples were immediately centrifuged in GYROZEN 406 Centrifuge machine (Gyrozen Co. Ltd. Korea) following the centrifugal protocol for A-PRF (n=20) and L-PRF (n=20). Within the limitation of the study we concluded that LyoplantÂ® showed superior tensile strength than L-PRF which in turn showed superior tensile strength than A-PRF. Based on the available information, it can be said that PRF is a healing biomaterial that can be used in regenerative surgical operations to speed healing, however its suitability as a barrier membrane is questionable given its inferior mechanical qualities.
Keywords: L-PRF; A-PRF; LSCC; Tensile Strength and Mechanical Properties